Innovative Teaching Technology for Optimum Skill Development; The Paradigm Shift towards Quality Education as per NEP - Dr. Sanjeev Saxena (International Journal of Engineering and Management Research, 2020)
What we are practicing today constitutes a traditional style of learning where as new education policy 2020 is looking forward to emphasize upon increasing GER & developing employable skills in the students through optimum learning methods. Since necessity is the mother of invention, so we need innovative learning pedagogy at distinct stages of education i.e. Primary Level, Secondary Level and Higher Education Level. As different age group learners get education at different aforesaid levels and therefore pedagogical styles may vary at Primary, Secondary & Higher Education level of education. Traditional teachers centric pedagogy as on today is gradually shifting towards more effective Learner’s Centric Pedagogy which provides learners a stress free environment, More flexibility and a greater participation than ever before in the history of learning. The paper attempts to investigate most recent innovative teaching practices and futuristic approaches particularly at Higher Education Level (Student Age 16 & above), that would help in developing employable skills in the learners to cater industrial needs. I wish to urge top decision makers to think a while over the findings of the paper for academic excellence especially in the context of higher education.